The role of the pseudoexfoliative syndrome as a transitional entity to glaucoma - Orozco, Cesar Alberto Ortiz; Gutiérrez, Felix Osuna; Torres, José María Zepeda; Fernandez, Carlos Navarro; Gomez, Adriana Baltazar; Aguilar, Sofia Vibiana Garcia; Garcia, Victor Manuel Elizarras (International Surgery Journal, 2022)
The balance between the secretion of aqueous humor by the ciliary body and its drainage through 2 independent pathways, the trabecular meshwork and the uveoscleral outflow pathway; and this will determine the intraocular pressure, which is considered the determining factor for glaucoma. Glaucoma is an entity of great clinical importance, being the second cause of blindness worldwide. There are different explanations for the pathophysiology of the disease, as well as immunological and vascular factors that lead to an increase in intraocular pressure, causing all these factors to trigger the development of glaucoma. Pseudoexfoliation syndrome can be defined as a systemic pathology that is generated by the deposition of extracellular fibrillar material in different tissues, and which, depending on the affected person, can cause different subsequent entities. Glaucoma progression and its sequelae may be more related to higher intraocular pressures than to other mechanisms. Various studies relate oxidative stress to glaucomatous progression. As the composition of the material causing pseudoexfoliation is further studied, its influence on the eye can be better understood.